Produção de lipase por Candida tropicalis URM 7057 utilizando biorreator tanque agitado - Silva, Renata Kelly Pereira da (2019)
The enzymes Lipases (triacylglycerol hydrolases, EC 3.1.1.3) are ubiquitous, have considerable physiological significance and industrial potential, are the most used biocatalysts in organic synthesis, because they are neither environmentally hazardous nor toxic in nature, they provide more solutions clean and more suitable for the synthesis of chemicals compared to catalysts of chemical origin. The high costs of the commercial enzymatic extracts intensify the studies aiming at cheapening the production, from the optimization of the enzymatic production in order to increase the competitiveness with the chemical catalysts. Thus, the objective of this study was to maximize lipase enzyme production using alternative sources of carbon, nitrogen and inducer, and as a differential, from the aerated culture in agitated tank bioradulator in batch and fed batch. Cultures using Candida tropicalis URM 7057 were carried out in a 5 L bioreactor whose culture medium consisted of 5.0 g L -1 sugar cane molasses, carbon source, 6.0 g L-1 protein maize maceration water (CSL), nitrogen source, 0.5% v / v olive oil (OMW) waste water, inducer, 0.5 g L-1 ammonium sulfate and 3.0 g L -1 of peptone in potassium phosphate buffer at pH 7.0 at 30 ° C and 300 rpm for 72 hours, evaluating the inoculum time (4 and 24 hours), the different oxygen transfer fluxes (without forced aeration, 0.25 and 0.75 vvm), the effect of the initial glucose concentration (2.5 and 5.0 g L-1) in addition to the batch production fed from the addition of the inductor, wastewater from the olive oil mills. When transferring the inoculum still in the exponential phase of growth, there was a greater production of the enzyme in less time of culture. From the different oxygen transfer fluxes the most expressive result was found in the condition of 0.75 vvm resulting in 2062.48 ± 163.41 U L-1 in 60 h of culture. Glucose concentration (2.5 g L-1) restricted lipase production. In the batch fed there was an increase in cell growth and maximum total activity 2724.48 ± 70.11 U L-1 in 120 h of culture. With the study, the enzymatic activity of lipase was increased from the new perspectives and strategies used.